Answer:
2y + 3x = -17
Explanation:
standard form is Ax + By = C
first step is to distribute -3/2 among 'x' and then by 1 to get:
-3/2x - 3/2
you now have y + 7 = -3/2x - 3/2
we want to get the -3/2x term on the same side as 'y' and get 7 from the right side to the left side
we want to add 3/2x to the left side of the equation because it is being subtracted:
y + 3.2x + 7 = -3/2
now we want to subtract 7 to the right side because it is currently being added:
y + 3/2x = -7 3/2
we can convert -7 3/2 to be -17/2
we now can eliminate the denominator of 2 in the 'x' term by multiplying each term by 2 to get:
2(y + 3/2x) = -17/2(2)
distribute and simplify to get:
2y + 3x = -17